Investigation of different aspects of the side-coupled cavities type interaction structures for the slow wave high power electron beam devices - Tripathi, Prabhakar (IIT(BHU) Varanasi, 2020)
Abstract is available in content.
Keywords: Investigation of different aspects of the side-coupled; cavities type interaction structures for the slow; wave high power electron beam devices